CGIAR in Vietnam: Working together to achieve food, land and water systems transformation - CGIAR (CGIAR System Organization, 2021)
This video captures key highlights of CGIAR achievements from 2018 to 2021 in Vietnam and was shared at the 3rd coordination meeting between the Ministry of Agriculture and Rural Development of Vietnam and CGIAR on 10 December 2021